Long-acting or extended-release antiretroviral products for HIV treatment and prevention in infants, children, adolescents, and pregnant and breastfeeding women: knowledge gaps and research priorities. Issue 8 (August 2019) - Nachman, Sharon; Townsend, Claire L; Abrams, Elaine J; Archary, Moherndren; Capparelli, Edmund; Clayden, Polly; Lockman, Shahin; Jean-Philippe, Patrick; Mayer, Kenneth; Mirochnick, Mark; McKenzie-White, Jane; Struble, Kimberly; et al.
Summary: Antiretroviral agents with long-acting properties have potential to improve treatment outcomes substantially for people living with HIV. In November 2017, the Long acting/Extended Release Antiretroviral Resource Program (LEAP) convened a workshop with the aim of shaping the research agenda and promoting early development of long-acting or extended release products for key populations: pregnant and lactating women, children aged up to 10 years, and adolescents aged 10–19 years. Goals included strategies and principles to ensure that the needs of children, adolescents, and pregnant and lactating women are considered when developing long-acting formulations. Research should focus not only on how best to transition long-acting products to these populations, but also on early engagement across sectors and among stakeholders. A parallel rather than sequential approach is needed when establishing adult, adolescent, and paediatric clinical trials and seeking regulatory approval. Pregnant and lactating women should be included in adult clinical trials. Adolescent-friendly trial design is needed to improve recruitment and retention of young people.